A Comparison of Perineal Myocutaneous Flaps Following Abdominoperineal Excision of the Rectum for Anorectal Pathology. Issue 11 (13th December 2021) - Tiernan, Jim P.; Leavitt, Tripp; Sapci, Ipek; Valente, Michael A.; Delaney, Conor P.; Steele, Scott R.; Gorgun, Emre
Abstract : BACKGROUND: Flap-based reconstruction following abdominoperineal resection has been used to address the resultant soft tissue defect and reduce postoperative wound complications. Vertical rectus abdominis myocutaneous flaps have been the traditional choice, but locoregional flaps have attracted attention in minimally invasive resection because they avoid additional abdominal dissection. However, few data exist comparing flap types. OBJECTIVE: To compare outcomes for different types of perineal reconstruction in patients undergoing abdominoperineal resection exclusively for anorectal pathology. DESIGN: This was a retrospective comparative study. SETTING: This study was conducted at a large, tertiary referral institution. PATIENTS: Following Institutional Review Board approval, prospectively maintained clinical and financial databases were interrogated and cross-referenced for patients undergoing proctectomy or abdominoperineal resection with flap reconstruction from 2007 to 2018. Patients with primary gynecological or urological pathology were excluded. MAIN OUTCOME MEASURES: The primary outcome was flap complication rate. Secondary outcomes included perineal hernia rate, donor site complications, emergency department consult after discharge, readmission <90 days, and length of stay. Data were analyzed using univariate and multivariate techniques. RESULTS: A total of 135 patients (79 female, median age 58 years) were included: 68 rectus, 52 gluteal, and 15 gracilis flap reconstructions. Median follow-up was 46 months. Rates of both major and minor flap complications were similar for rectus and gluteal flaps, even when controlling for differences between groups via multivariate analysis ( p > 0.9), including extent of resection and use of mesh. For all flaps, American Society of Anesthesiology score ≥3 was the only independent predictor of major, but not minor, flap complications. For rectus and gluteal flaps, smoking, female sex, and American Society of Anesthesiology score ≥3 were independent predictors of major flap complications ( p < 0.05). LIMITATIONS: This study was limited by its retrospective nature and potential selection bias associated with flap choice; it was also impossible to quantify defect size. CONCLUSION: Gluteal flaps have similar complication rates to rectus flaps and may be considered for patients who are otherwise suitable for minimally invasive abdominoperineal resection. See Video Abstract at http://links.lww.com/DCR/B866 . Una comparación de los colgajos miocutáneos perineales después de la escisión abdominoperineal del recto para patología anorectal ANTECEDENTES: La reconstrucción con colgajo después de la resección abdominoperineal se ha utilizado para abordar el defecto de tejido blando resultante y reducir las complicaciones postoperatorias de la herida. Los colgajos miocutáneos verticales del recto abdominal han sido la elección tradicional, pero los colgajos locorregionales han atraído la atención en la resección mínimamente invasiva porque evitan la disección abdominal adicional. Sin embargo, existen pocos datos que comparen los tipos de colgajos. OBJETIVO: Comparar los resultados de diferentes tipos de reconstrucción perineal en pacientes sometidos a resección abdominoperineal exclusivamente por patología anorrectal. DISEÑO: Este fue un estudio comparativo retrospectivo. ENTORNO CLÍNICO: Este estudio se llevó a cabo en una gran institución de referencia terciaria. PACIENTES: Tras la aprobación de la Junta de Revisión Institucional, las bases de datos clínicas y financieras mantenidas de forma prospectiva fueron interrogadas y cruzadas para pacientes sometidos a proctectomía o resección abdominoperineal con reconstrucción con colgajo de 2007 a 2018. Se excluyeron pacientes con patología ginecológica o urológica primaria. PRINCIPALES MEDIDAS DE RESULTADO: El resultado primario fue la tasa de complicaciones del colgajo. Los resultados secundarios incluyeron la tasa de hernia perineal, las complicaciones del sitio donante, la consulta en el departamento de emergencias posterior al alta, la readmisión <90 días y la duración de la estancia intrahospitalaria. Los datos se analizaron mediante técnicas univariadas y multivariadas. RESULTADOS: Se incluyeron un total de 135 pacientes (79 mujeres, mediana de edad 58 años): 68 reconstrucciones de recto, 52 de glúteo y 15 de colgajo de gracilis. La mediana de seguimiento fue de 46 meses. Las tasas de complicaciones mayores y menores del colgajo fueron similares para los colgajos de recto y glúteo, incluso cuando se controlaron las diferencias entre los grupos mediante un análisis multivariado ( p > 0, 9), incluida la extensión de la resección y el uso de malla. Para todos los colgajos, la puntuación ≥3 de la American Society of Anesthesiology fue el único predictor independiente de complicaciones mayores, pero no menores. Para los colgajos de recto y glúteo, el tabaquismo, el sexo femenino y la puntuación ≥3 de la Sociedad Americana de Anestesiología fueron predictores independientes de complicaciones mayores del colgajo ( p < 0, 05). LIMITACIONES: Este estudio estuvo limitado por su naturaleza retrospectiva; imposible cuantificar el tamaño del defecto; sesgo de selección potencial asociado con la elección del colgajo. CONCLUSIÓN: Los colgajos de glúteos tienen tasas de complicación similares a los colgajos de recto y pueden considerarse para pacientes que, por lo demás, son aptos para una resección abdominoperineal mínimamente invasiva. Consulte Video Resumen en http://links.lww.com/DCR/B866 . (Traducción—Dr. Berrones-Medina )